2011
DOI: 10.1002/hyp.8196
|View full text |Cite
|
Sign up to set email alerts
|

Exploring effects of rainfall intensity and duration on soil erosion at the catchment scale using openLISEM: Prado catchment, SE Spain

Abstract: Abstract:In semi-arid areas, high-intensity rainfall events are often held responsible for the main part of soil erosion. Long-term landscape evolution models usually use average annual rainfall as input, making the evaluation of single events impossible. Event-based soil erosion models are better suited for this purpose but cannot be used to simulate longer timescales and are usually applied to plots or small catchments. In this study, the openLISEM event-based erosion model was applied to the medium-sized (¾… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 71 publications
4
82
0
Order By: Relevance
“…6a) spanned only around 73% of the simulation time, it delivered 98.4% (99.9%, modeled) of the total sediment yield. This is in line with previously reported results from both field (Fu, 1989) and modeling experiments (Baartman et al, 2012;Zhang et al, 2012) that have shown that a few extreme events may contribute to a large portion of annual total soil erosion. Notably, our research area has a temperate weather and lacks extreme precipitation events, but nonetheless the dry period (~27% of the total simulation time) delivered only~1% of the total SSY.…”
Section: Temporal Variations In Modeled Estimatessupporting
confidence: 93%
“…6a) spanned only around 73% of the simulation time, it delivered 98.4% (99.9%, modeled) of the total sediment yield. This is in line with previously reported results from both field (Fu, 1989) and modeling experiments (Baartman et al, 2012;Zhang et al, 2012) that have shown that a few extreme events may contribute to a large portion of annual total soil erosion. Notably, our research area has a temperate weather and lacks extreme precipitation events, but nonetheless the dry period (~27% of the total simulation time) delivered only~1% of the total SSY.…”
Section: Temporal Variations In Modeled Estimatessupporting
confidence: 93%
“…6). It is likely that the combination of large amounts of antecedent precipitation and high precipitation intensities lead to a large amount of sediment detachment and enough overland flow to transport these sediments, as also shown in other studies in Spain (Baartman et al, 2012;Cantón et al, 2001;Giménez et al, 2012;Gómez-Plaza et al, 2001). Giménez et al (2012) furthermore, argued that most of the sediments at the outlet of the Latxaga catchment seemed to have come from areas close to the drainage network, which agrees with our findings.…”
Section: Factors Controlling Hillslope-channel Connectivitysupporting
confidence: 92%
“…A thorough understanding of gully erosion with respect to local climatic conditions is essential for effective planning, land management and conservation (Poesen et al, 2003). The impacts of climatic and meteorological factors on gully erosion has been widely studied (Nearing et al, 2005;Poesen et al, 2003) through modeling (Baartman et al, 2012;Favis-Mortlock and Boardman, 1995;Li et al, 2011;van Oost et al, 2000;Williams et al, 1996), laboratory experiments (Berger et al, 2010;el Kateb et al, 2013;Römkens et al, 2002), and field studies (Angel et al, 2005;Baartman et al, 2012;Capra et al, 2009;Hancock and Evans, 2010;Smith and Dragovich, 2008;Wei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated the relationship between precipitation intensity and soil erosion at the plot scale under natural precipitation conditions over several years (Baartman et al, 2012;Keay-Bright and Boardman, 2009;Porto et al, 2014;Wei et al, 2010). Capra et al (2009) investigated the relationship between gully erosion and the precipitation erosivity factor in a cultivated catchment in Italy at a yearly scale.…”
Section: Introductionmentioning
confidence: 99%